Therapeutic drug monitoring practices of anti-infectives: An Asia-wide cross-sectional survey - Hou, Jingjing; Marriott, Debbie; Cattaneo, Dario; Stocker, Sophie; Stojanova, Jana; Alffenaar, Jan-Willem; Xiao, Chenlin; Zhao, Yichang; Gong, Hui; Yan, Miao (Frontiers in Pharmacology, 2022)
Objectives The current practice of therapeutic drug monitoring (TDM) in Asia is poorly documented. Our aim was to capture and describe TDM services delivered in hospitals across Asia, including aspects such as assay availability, interpretation of results and clinical decision-making. Methods An online survey about anti-infective TDM practices, available in English and involving 50 questions, was promoted to people involved in TDM in Asia. The survey was open for responses from September to November 2021. Results Of 207 responses from participants working in 14 Asian countries, 150 responses from 10 countries could be included. TDM services are available for many anti-infectives, providing assays based on chromatographic assays (100.0%) or immunoassays (39.3%). Clinicians (82.6%) and pharmacists (86.8%) were responsible for ordering and interpreting TDM. Most services provided reference targets and dose recommendations. Interpretative support was available to a varying degree. Assay results were available and clinical decision-making could be completed within 24 hours in most hospitals (87.9% and 88.9% respectively). As the turnaround time of assay results decreased, the proportion of clinical decision-making completed within 8 hours increased. Barriers to implementation of TDM included lack of funding or equipment (71.1%), lack of clinician interest or cooperation (47.0%), and lack of expertise (42.3%). Lack of expertise was the primary barrier for using precision dosing software (50.5%). Conclusions There are significant differences and challenges in the development and practice of anti-infective TDM in Asian countries.